Mobile origami immunosensors for the rapid detection of urinary tract infections. Issue 24 (6th October 2020) - Adrover-Jaume, Cristina; Rojo-Molinero, Estrella; Clemente, Antonio; Russell, Steven M.; Arranz, Javier; Oliver, Antonio; de la Rica, Roberto
Abstract : Immunosensors made of paper interfaced with smartphones diagnose UTIs in less than 10 minutes. Abstract : Urinary tract infections (UTI) have a high prevalence and can yield poor patient outcomes if they progress to urosepsis. Here we introduce mobile origami biosensors that detect UTIs caused by E. coli at the bedside in less than 7 minutes. The origami biosensors are made of a single piece of paper that contains antibody-decorated nanoparticles. When the urine sample contains E. coli, the biosensors generate colored spots on the paper strip. These are then quantified with a mobile app that calculates the pixel intensity in real time. The tests are highly specific and do not cross-react with other common uropathogens. Furthermore, the biosensors only yielded one false negative result when queried with a panel containing 57 urine samples from patients, which demonstrates that they have excellent sensitivity and specificity. This, along with the rapid assay time and smartphone-based detection, makes them useful for aiding in the diagnosis of UTIs at the point of care.